Accounting policy as a tool for modeling the mechanism of application of elements of the method of accounting services in the field of business security - O.Yu. Shyrokopoias (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Depending on the industry in which the enterprise operates, specific accounting policies will be identified. According to the study, the process of forming accounting policies for businesses providing services in the field of business security will be specific. It is established that it is not possible to form a unified approach to the policy-making of the enterprises of the industry, since different types of security services result in different range of accounting objects, cost structure, choice of accounting methods and cost calculation, structuring of direct and indirect, fixed and variable costs. It is determined that accounting policy is an effective tool for managing information flows that are formed in the system of managing the business activity of an enterprise, which provides services in the field of business security. The article investigates the essence of the concept of accounting policy and formed its own definition of the concept i.e. a tool for the formation of information space management service in the field of business security, which determines the order of accounting and the choice of mechanisms for applying the elements of accounting method, which are provided by law, taking into account the specifics of the control. In the course of the research, a model of accounting was constructed as a process of modeling economic reality. It is established that modeling as a method of scientific research in accounting allows identifying the properties of the accounting object, which determine the features of its reflection in accounting; forming an ideal model of business management information support, based on identified user requests, both internal and external.